Comparative study on renegeneration of spent actived carbon by chemical and termal treatments - Fadzlie Fauzi (School of Environmental Engineering, University Malaysia Perlis, 2013)
The objective in this study to evaluate the performance of spent activated carbon after regeneration by chemical and thermal treatments. Two methods of regeneration had been used for this study which is chemical regeneration and thermal regeneration.